Cross-cultural adaptation and validation of the International Cooperative Ataxia Rating Scale (ICARS) to Brazilian Portuguese - Maggi, Fernanda Aparecida; Braga-Neto, Pedro; Chien, Hsin Fen; Drumond Gama, Maria Thereza; Rezende Filho, Flavio Moura; Saraiva-Pereira, Maria Luiza; Jardim, Laura Bannach; Voos, Mariana Callil; Pedroso, Jose Luiz; Povoas Barsottini, Orlando Graziani (Assoc Arquivos Neuro- Psiquiatria, 2018)
Introduction: The clinical assessment of patients with ataxias requires reliable scales. We aimed to translate, adapt and validate the International Cooperative Ataxia Rating Scale (ICARS) into Brazilian Portuguese. Methods: The steps of this study were forward translation, translation synthesis, backward translation, expert committee meeting, preliminary pilot testing and final assessment. Thirty patients were enrolled in the preliminary pilot testing and 61 patients were evaluated for construct validity, internal consistency, intra- and inter-rater reliability and external consistency. Results: This study showed good validity of the construct and high internal consistency for the full scale, except for the oculomotor domain (Cronbach's alpha = 0.316, intraclass correlation coefficients intra- = 82.4% and inter- = 79.2%).A high correlation with the Scale for the Assessment and Rating of Ataxia was observed. We found good intra-rater agreement and relative inter-rater disagreement, except in the posture and gait domain. Conclusion: The present ICARS version is adapted for the Brazilian culture and can be used to assess our ataxic patients.
Keywords: Spinocerebellar ataxias; translating; validation studies